The intestine: A highly dynamic microenvironment for IgA plasma cells - Pracht, Katharina; Wittner, Jens; Kagerer, Fritz; Jäck, Hans-Martin; Schuh, Wolfgang (Frontiers in Immunology, 2023)
To achieve longevity, IgA plasma cells require a sophisticated anatomical microenvironment that provides cytokines, cell-cell contacts, and nutrients as well as metabolites. The intestinal epithelium harbors cells with distinct functions and represents an important defense line. Anti-microbial peptide-producing paneth cells, mucus-secreting goblet cells and antigen-transporting microfold (M) cells cooperate to build a protective barrier against pathogens. In addition, intestinal epithelial cells are instrumental in the transcytosis of IgA to the gut lumen, and support plasma cell survival by producing the cytokines APRIL and BAFF. Moreover, nutrients are sensed through specialized receptors such as the aryl hydrocarbon receptor (AhR) by both, intestinal epithelial cells and immune cells. However, the intestinal epithelium is highly dynamic with a high cellular turn-over rate and exposure to changing microbiota and nutritional factors. In this review, we discuss the spatial interplay of the intestinal epithelium with plasma cells and its potential contribution to IgA plasma cell generation, homing, and longevity. Moreover, we describe the impact of nutritional AhR ligands on intestinal epithelial cell-IgA plasma cell interaction. Finally, we introduce spatial transcriptomics as a new technology to address open questions in intestinal IgA plasma cell biology.